2017
DOI: 10.1038/s41467-017-00453-3
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate discovery and replication of five novel loci associated with Immunoglobulin G N-glycosylation

Abstract: Joint modeling of a number of phenotypes using multivariate methods has often been neglected in genome-wide association studies and if used, replication has not been sought. Modern omics technologies allow characterization of functional phenomena using a large number of related phenotype measures, which can benefit from such joint analysis. Here, we report a multivariate genome-wide association studies of 23 immunoglobulin G (IgG) N-glycosylation phenotypes. In the discovery cohort, our multi-phenotype method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
130
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(139 citation statements)
references
References 41 publications
9
130
0
Order By: Relevance
“…We and others identified several loci associated with IgG and plasma glycosylation and autoimmune conditions in the previous GWAS 24,25,31,32 , so we wanted to relate those findings to the genetic background of the subjects in this study to determine whether there is a shared heritability of AITD and IgG N-glycan traits. We estimated the proportions of genetic and environmental variance in the phenotypic variation of AITD status and different IgG N-glycan traits using the twin data from the TwinsUK cohort and the maximum likelihood variance component model fitting, also known as a structural equation-modeling or ADCE model 33 Supplementary Table 6), as previously estimated in a Danish twin cohort [25][26][27] .…”
Section: Mackia Amurensis Lectin (Mal-ii) Phaseolus Vulgaris Erythromentioning
confidence: 99%
See 1 more Smart Citation
“…We and others identified several loci associated with IgG and plasma glycosylation and autoimmune conditions in the previous GWAS 24,25,31,32 , so we wanted to relate those findings to the genetic background of the subjects in this study to determine whether there is a shared heritability of AITD and IgG N-glycan traits. We estimated the proportions of genetic and environmental variance in the phenotypic variation of AITD status and different IgG N-glycan traits using the twin data from the TwinsUK cohort and the maximum likelihood variance component model fitting, also known as a structural equation-modeling or ADCE model 33 Supplementary Table 6), as previously estimated in a Danish twin cohort [25][26][27] .…”
Section: Mackia Amurensis Lectin (Mal-ii) Phaseolus Vulgaris Erythromentioning
confidence: 99%
“…On the other hand, it was observed that among HT, GD, and PTC groups, HT patients had significantly lower core fucose content on TgAb than the other two groups 22 . Furthermore, since recent genome-wide association studies (GWAS) identified novel loci associated with IgG glycosylation, which were known to be strongly associated with autoimmune conditions 23,24 and the heritability of AITD is estimated to 55-75% [25][26][27] , the next logical step was to examine if there was any common genetic background between those…”
Section: Introductionmentioning
confidence: 99%
“…Cichonska et al [11] 55 get CCA results using summary-level data, but how to interpret and replicate CCA 56 results are not thoroughly discussed. Based on CCA, using individual-level data, we 57 introduced a combined phenotype score to assess the genetic effect so that the 58 replication can be meaningful [12]. More importantly, what geneticists want to acquire 59 from multi-trait analyses is additional knowledge about pleiotropy, while such an aim is 60 February 22, 2019 4/27 hardly reached by current multivariate methods.…”
mentioning
confidence: 99%
“…For the 23 loci replicated by the MVA-significance test, to test the consistency of 284 pleiotropic effects, we implemented two novel replication strategies as follow-up methods 285 of the MVA-significance replication: MVA-score replication, which we previously 286 developed for individual-level data analysis [12], and MC-based correlation replication 287 (S1 Fig). The MVA-score replication integrates the multivariate genetic effects into the 288 genetic effect on MVA-score, and aims to replicate the discovered locus pleiotropic 289 profile by testing this integrated effect; while the MC-based correlation replication tests 290 the consistency of multivariate genetic effects directly.…”
mentioning
confidence: 99%
See 1 more Smart Citation